Competência sancionatória nos contratos administrativos - Candido, Daniele Chamma (2009)
This paper has a proposal of delimiting the legal regime of penalties applicable to individuals that celebrates administrative contracts with Public Administration. In order to do that, we analyze the legal relationship between parts in an administrative contract, its legal basis, purpose and peculiarities. Next, we try to locate the applicable penalties in the administrative contracts within the universe of all the penalties available to State by the legal system, highlighting the peculiarities of the legal system applicable to them. So, the administrative contract must be recognized with sort of special relationship of submission, which means, a link that generates a specific legal situation, where the contractor assumes the obligation to comply with the contract, its established rules and the possible changes that may occur in the amendment. The individual s contact with the Public Administration, through the contractual relationship, demands an internal discipline in order to ensure their proper exercise. This internal discipline is in charge of the Administration because it is impossible to the legislator to predict all the requirements for a successful implementation of all the administrative contracts and also because a general forecast of such would eliminate entirely the freedom of the Administration to amend the contract terms, as changing the public interest subjacent. One of the privilege conferred to the Administration in relation to the existing special entry in the administrative contract is the competence penalty, which means, the legal authorization to punish individuals that breaks their duties voluntarily assumed by the administrative contract. In the case of special circumstances for entry, the constitutional principles that limit the activity of the State penalty are flexible and shall apply in a more elastic manner. Thus, the law gives the power to sanction a plea, but not necessarily typifies the offenses and penalties. These can then be governed by rules, such as in the cases of agencies, for example or may be established in the contract. The typification is required, but not in the legal level, with no unconstitutionality in such a legal regime